Phytosanitation: A novel approach toward disease management - de Freitas Bueno, Regiane Cristina Oliveira [UNESP]; Ansari, Rizwan Ali; Lima, Giuseppina Pace Pereira [UNESP]; Sakate, Renate Krause [UNESP] (Springer Nature, 2019)
For millennia, man has been producing food, using agriculture, but with increasing cultivated areas, due to the increasing need for food, problems related to production, especially the increase of insect pests, diseases of plants and interferences with weed plants also multiplied. The evolution of plants, through a better genetic approach, transformed the terrestrial environment, making them a very valuable resource for the herbivore community. In ecosystems, plants and insects are just some of the living organisms that continually interact in complex ways and may be the most complex relationships observed in nature. The generated effects of this interaction may be beneficial or harmful to both. To avoid insect attack, plants have developed different mechanisms, such as physical and chemical barriers, defense proteins, volatile substances, secondary metabolism, and trichomes. On the other hand, the insects developed different patterns of associations with host plants, together with different feeding strategies necessary for the exploration of the hosts. Herbivorous insects present complementary adaptations as a response to each defense adaptation in host plants. It is clear that insects are successful in terms of number of species and size of population and as the chemical composition of plants is variable, this represents a challenge for insect feeding. However, insects possess a powerful set of enzymes that constitute the defense against toxic chemicals produced by plants.
Keywords: Crop protection; Entomology; Insect plant interaction; Integrated pest management; Plant physiological stress